Assembly of hepatitis E vaccine by 'in situ' growth of gold clusters as nano-adjuvants: an efficient way to enhance the immune responses of vaccination. Issue 5 (27th June 2016) - Wang, Hai; Ding, Yanping; Su, Shishuai; Meng, Duojia; Mujeeb, Ayeesha; Wu, Yan; Nie, Guangjun
Abstract : Vaccine-based immunotherapy plays an integral role in the development of present and future clinical therapies. Abstract : Vaccine-based immunotherapy plays an integral role in the development of present and future clinical therapies. Despite the success, there is still a great need to improve the efficiency and safety of vaccines. Nanoparticles have been widely used for improving the efficacy of vaccines by encapsulating the vaccines or using nanoparticles as immune adjuvants. However, the methods for the preparation of nanoparticles are complex with a relatively low encapsulation efficiency of protein vaccine inside the nanocarriers and/or undefined physiochemical properties. Here, we report a new method of preparation of a vaccine by the " in situ " growth of gold clusters in the hepatitis E vaccine (HEVA). The gold cluster grafted HEVA (HEVA/Au) can be easily obtained and there is no loss of HEVA during the preparation process. More importantly, the " in situ " prepared HEVA/Au can not only enhance its immune responses in vivo, but also reduce the potential toxicity of HEVA. Furthermore, the intrinsic fluorescence of gold clusters enables the HEVA to be traceable, which may open a way to track the dynamic behavior of vaccines and further help to optimize an individual therapeutic regimen for immunotherapy.